Pengaruh Kredit Cepat Aman (KCA) Terhadap Pendapatan Sewa Modal Pada PT Pegadaian (PERSERO) - Jusuf Nurdin; Nuniek Dewi Pramanik; Euis Hernawati; Wiwi Warsiati (Journal on Education, 2023)
Kredit Cepat Aman (KCA) is an excellent product of PT Pegadaian which is distributed to the public with collateral of valuables and has a capital lease term based on a certain rate and a certain period of time that the customer must pay for the loan he receives. The purpose of this research is to determine the effect of Kredit Cepat Aman (KCA) on capital lease income at PT Pegadaian (Persero) period years 2017-2021. The method used in this research is quantitative with simple linear regression analysis. Data collection techniques in this research are observation, documentation, literature study and internet browsing. The results of the research show that Kredit Cepat Aman (KCA) and capital lease income from 2017-2021 increase every year and decrease in 2021. Kredit Cepat Aman (KCA) has a very strong influence, is positive or there is a significant unidirectional relationship to capital lease income.